2020
DOI: 10.15766/mep_2374-8265.10899
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Treatment of Opioid Withdrawal and Opioid Use Disorder in the Emergency Department

Abstract: Introduction: Opioid addiction and misuse constitute a public health crisis in the United States. Recent research supports buprenorphine induction in the emergency department (ED) setting for patients with opioid use disorder (OUD). However, education regarding buprenorphine induction for emergency medicine (EM) physicians, residents, and students is still limited. Methods: We created a 1-hour introductory workshop for the identification and treatment of opioid withdrawal and OUD in the ED for medical students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…[18][19][20] While curricular initiatives focused on opioid use disorder are growing in number, we are not aware of any other curriculum that offers teaching on OEND with a direct application of learning in the clinical environment. [21][22][23][24] This novelty of our curriculum provides an engaging learning experience and a real impact for the clinical team.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] While curricular initiatives focused on opioid use disorder are growing in number, we are not aware of any other curriculum that offers teaching on OEND with a direct application of learning in the clinical environment. [21][22][23][24] This novelty of our curriculum provides an engaging learning experience and a real impact for the clinical team.…”
Section: Introductionmentioning
confidence: 99%
“…In one survey, 77% of residency program directors reported that residents frequently cared for patients with OUD, yet only 23% reported spending 12 or more hours of curricular time on addiction. 8 Furthermore, most prior educational interventions on OAT are based in outpatient settings [9][10][11] or the emergency department 12 rather than the inpatient setting. There have been no prior studies of educational interventions aimed at broadly teaching all IM residents within a program to manage OAT in the inpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…Didactic and skills sessions for internal medicine, family medicine, and emergency medicine residents have shown that specific training, such as naloxone training, is effective in improving overall comfort in caring for adults with opioid use disorder and change in clinical practice [13][14][15][16]. Given the success of dedicated curricula for trainees of other specialties regarding adult opioid use disorder, we developed a clinically translatable curriculum for pediatric and family medicine residents to specifically identify and treat AYA opioid dependence and withdrawal in pediatric patients, with hopes of improving resident comfort treating opioid use disorder and addiction in clinical practice.…”
Section: Introductionmentioning
confidence: 99%